Pemberdayaan Walikelas Untuk Meningkatkan Partisipasi Siswa Dalam Melaksanakan PJJ Ramadhan - Hema Hujaemah (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The Covid-19 pandemic, which has spread in almost all parts of Indonesia, has not yet been declared complete. So that it has a big influence on the learning system in schools. Distance learning (PJJ) is the most appropriate way in this situation. Likewise with PJJ in the month of Ramadan this year, different from previous years. The role of the principal and the class guardian is so important so that the learning process continues to run well. The low level of student participation in the first week of PJJ in Ramadan 1441 H is the background of this research. The purpose of this research is to increase student participation in carrying out PJJ Ramadhan in the Covid-19 era. Empowerment of classmates through Google classroom, WhatsApp and other media is used as the method in this research. So that the following results were obtained: there was an increase in the participation of class VII students who joined the Google classroom by 14%, class VIII students 8%, while class VII who submitted assignments, increased by 50%, class VIII was 90% of the number of students who submitted assignments on Cycle 1. So it can be concluded that the empowerment of the teacher through Google classroom, WhatsApp and other media can be chosen as a solution to overcome the problem of student participation that is still lacking. Motivation and support from all parties can increase student participation rates.